1989
DOI: 10.1021/ja00208a002
|View full text |Cite
|
Sign up to set email alerts
|

Thermochemical properties of gas-phase MgOH and MgO determined by Fourier transform mass spectrometry

Abstract: Gas-phase thermochemical values £>°(Mg+-OH) = 75 ± 4 kcal/mol, IP(MgOH) = 7.3 ± 0.1 eV, D°(Mg+-0) = 53 ± 3 kcal/mol, and IP(MgO) = 7.9 ±0.1 eV have been experimentally determined by photodissociation measurements and charge-transfer reactions with Fourier transform mass spectrometry. These results, together with previously determined thermochemical data, are used to determine other thermochemical properties of MgOH and MgO. Our value Z)°(Mg-OH) = 67 ± 6 kcal/mol agrees well with previous experimental values. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
36
1
4

Year Published

1998
1998
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(48 citation statements)
references
References 0 publications
7
36
1
4
Order By: Relevance
“…footnotes in Table 8). Later, an experimental thermodynamic dissociation energy (all atoms in their ground states) was found in the literature [44], which is in accordance with B3LYP as well as the ACPF calculations. Thus, the MgO problem is solved.…”
Section: Concluding Remarks On Calculated Versus Experimental Propertsupporting
confidence: 81%
“…footnotes in Table 8). Later, an experimental thermodynamic dissociation energy (all atoms in their ground states) was found in the literature [44], which is in accordance with B3LYP as well as the ACPF calculations. Thus, the MgO problem is solved.…”
Section: Concluding Remarks On Calculated Versus Experimental Propertsupporting
confidence: 81%
“…While both pseudopotentials give excellent agreement to the experimental bond length and electron affinity, we find some difference for the binding energy and the ionization energy. Using a He-core, rather than Ne-core, pseudopotential for Mg increases the molecular binding energy from 2.28±0.01 eV to 2.43±0.01 eV, in comparison to the experimental value of 2.54±0.22 eV [19,[46][47][48]. This suggests that allowing the Mg 2s and 2p electrons to participate in the bonding allows more recovery of the binding energy.…”
Section: Supplementary Information I Properties Of Mgo Molecule As Dmentioning
confidence: 75%
“…1 Unlike the earlier report by Freiser et al, 9 who found Mg + to be the only ionic product, these authors observed several dissociation channels leading to the formation of Mg + , CH 3 + , MgO + , and MgOH + . The last product is difficult to ascertain because of the overlap of the isotope peaks of 25 Mg and 26 Mg in the mass spectrum. Farrar and co-workers studied Sr + (CH 3 OH) and Sr + (CH 3 OD) using the photodissociation method.…”
Section: Introductionmentioning
confidence: 99%